2009
DOI: 10.1038/jid.2008.412
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Regimens of Topical Corticosteroids in the Treatment of Patients with Bullous Pemphigoid: A Multicenter Randomized Study

Abstract: Superpotent topical corticosteroids (CS) have been demonstrated to improve bullous pemphigoid (BP) patients' survival. We assessed whether a mild regimen using lower doses of topical CS and a shorter duration could improve the outcome of BP patients even more. Three-hundred and twelve BP patients were included in a multicenter randomized controlled trial and stratified depending on the extent of BP as moderate (n=134) or extensive (n=178). Patients were randomly assigned to the standard regimen (clobetasol pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
208
3
21

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 217 publications
(242 citation statements)
references
References 24 publications
10
208
3
21
Order By: Relevance
“…In experimental autoimmune encephalomyelitis, GM-CSF is required to sustain neuroinflammation via myeloid cells infiltrating the CNS (14). Given the rising incidence of autoimmune diseases in general and autoimmune bullous dermatoses specifically (53,54), the so far limited therapeutic options (55,56), and the high morbidity and mortality of the patients (54), there is a clear need for novel treatment strategies. In several autoimmune diseases, such as rheumatoid arthritis, inhibition of cytokines or growth factors has dramatically improved the management of these conditions (57)(58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…In experimental autoimmune encephalomyelitis, GM-CSF is required to sustain neuroinflammation via myeloid cells infiltrating the CNS (14). Given the rising incidence of autoimmune diseases in general and autoimmune bullous dermatoses specifically (53,54), the so far limited therapeutic options (55,56), and the high morbidity and mortality of the patients (54), there is a clear need for novel treatment strategies. In several autoimmune diseases, such as rheumatoid arthritis, inhibition of cytokines or growth factors has dramatically improved the management of these conditions (57)(58)(59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…Similar concerns about increased mortality and morbidity in bullous pemphigoid patients (that could be partly due to systemic therapies such as prednisolone), led to an RCT by Joly et al who found that mortality was reduced in those treated with potent topical steroids compared to those receiving systemic steroids. 11 The potential impact of PG on patients' quality of life is high. Baseline EQ-5D-3L scores of 0.59 (cohort study) and 0.48 (RCT) are comparable to patients with mild to severe heart failure; where EQ-5D-3L scores of 0.78 (SD 0.18) to 0.51 (SD 0.21) respectively have been reported.…”
Section: Main Findingsmentioning
confidence: 99%
“…Recently, lower doses of topical clobetasol propionate (10-30g daily) were shown to have similar short-term efficacy but reduced side-effects compared to the high dose topical regimen (40g daily clobetasol propionate) (Joly 2009). …”
Section: Topical Steroid Therapymentioning
confidence: 99%